Studies of the muon momentum calibration and performance of the ATLAS detector with pp collisions at √s=13 TeV - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2023)
This paper presents the muon momentum calibration and performance studies for the ATLAS detector based on the pp collisions data sample produced at sqrt{s}= 13 TeV at the LHC during Run 2 and corresponding to an integrated luminosity of 139 {\textrm{fb}}^{-1}. An innovative approach is used to correct for potential charge-dependent momentum biases related to the knowledge of the detector geometry, using the Z\rightarrow \mu ^{+}\mu ^{-}resonance. The muon momentum scale and resolution are measured using samples of J/\psi \rightarrow \mu ^{+}\mu ^{-}and Z\rightarrow \mu ^{+}\mu ^{-}events. A calibration procedure is defined and applied to simulated data to match the performance measured in real data. The calibration is validated using an independent sample of \Upsilon \rightarrow \mu ^{+}\mu ^{-}events. At the Z (J/\psi )peak, the momentum scale is measured with an uncertainty at the 0.05% (0.1%) level, and the resolution is measured with an uncertainty at the 1.5% (2%) level. The charge-dependent bias is removed with a dedicated in situ correction for momenta up to 450 GeV with a precision better than 0.03 {\textrm{TeV}}^{-1}.
ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassoff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2855 weitere]
Gesehen am 17.05.2024